(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2007)
It is not long time since globalization has started along with knowledge economy and, communication media and technical information control on the world. As a result serious events appeared like failure in businesses, financial corruption and shortage of administration and control. In spite of the great efforts held by international organizations and foundations to find organizational frames that adopt independence, questioning and transparency and comparison ability to secure audience rights and affording them valuable services ,but globalization in its rash towards change has lost social, vocational and administrative values .Even those who are in charge of business administration in large companies have lost those values that they misused companies’ finance by giving unreal and vague rates of companies and prices inflation for the companies they lead in a trail to raise the prices of stocks in financial markets or to keep them so. Therefore several ideas and suggestions for development and organization have been proposed by those in charge of accountancy and control affairs in western countries. But the influence of large companies has prevented their application. As a result breakdown crisis came to affirm the necessity of vocational reform, business organization and reviewing the services presented in one hand and focusing on systems and corporates governance standards and administration conducts in the other, to achieve world stability which is considered one of the basic goals of international society .This has become a critical necessity imposed by economics expansion and intermingling.